POSTCHOLECYSTECTOMY SYNDROME CAUSED BY VARIOUS DISORDERS OF INTESTINAL PERMEABILITY - Y. P. SAVCHENKO; V. M. BENSMAN; I. V. SUZDAL'CEV; G. K. KARIPIDI; V. A. GOLBRAIH; B. M. BELIK; N. J. KALININA; M. I. DENISOVA (Кубанский научный медицинский вестник)
Aim. This study was designed to prove the connection between postcholecystectomy syndrome, chronic disorder of duodenal patency, adhesive disease of the abdominal cavity, and  chronic colostasis and to develop the methods of its treatment.Materials and methods. During the period from 2004 to 2016 we monitored 140 patients with a clear picture of postcholecystectomy  syndrome which was manifested after the surgeries on the  extrahepatic biliary tract by clinic of passage disorders in the digestive tract.Results. The results of our study indicate that there are created a number of conditions that cause various pathologies in patients with  colostasis who have unfavorable outcomes after cholecystectomy.  Colostasis can cause functional changes in the biliary tract due to the overstretch of the colon areas by the accumulated contents.  Functional disturbances can be a consequence of the tension of the  mesocolon lowered by the transverse colon or duodenojejunal  ligament narrowing the lumen of the duodenum. The hepatic angle  of the large intestine in high position, deforming the bile duct and duodenum, can also cause postcholecystectomy syndrome.Conclusion. Long-term results of the surgical treatment of the pathological conditions after cholecystectomy depend not only on the condition of the organ which surgery was performed on but also on  other physiologically related organs and body systems. The biliary  and enteroenteric connections are very important in this case.  Psychosomatic disorders of the patient are also crucial while  assessing the long-term results of the surgical treatment of this type of patients. The results of the surgical treatment of the duodenal  patency chronic disorders depend on the selected type of surgery.  Thus, the exclusion of the duodenum from the food passage gives  better results than the surgeries aimed at improving the passage of  food through the duodenum. The choledochojejunostomy and  duodenoenterostomy are not effective. In the most severe cases of  duodenal patency chronic disorders two sided exclusion of the  duodenum with duodenenterostomy can be the only effective  method of its correction but the development of post-resection syndrome cannot be ruled out.